Search for the lightest scalar top quark in events with two leptons in p(p)over-bar collisions at root s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Alverson, G.; et al. (Elsevier B.V., 2009)
We report results of a search for the pair production of the lightest supersymmetric partner of the top quark, (t) over bar (1), using a data set corresponding to an integrated luminosity of 1 fb(-1) collected by the D circle divide detector at a p (p) over bar center-of-mass energy of 1.96 TeV at the Fermilab Tevatron collider. Both scalar top quarks are assumed to decay into a b quark, a charged lepton and a scalar neutrino. The search is performed in the electron Plus muon and dielectron final states. The signal topology consists of two isolated leptons, missing transverse energy, and jets. We find no evidence for this process and exclude regions of parameter space in the framework of the minimal supersymmetric standard model. (C) 2009 Elsevier B.V. All rights reserved.